Promotion of Phosphorus on Carbon Supports for MnOx−CeO2 Catalysts in Low‐Temperature NH3−SCR with Enhanced SO2 Resistance. Issue 15 (21st April 2021) - Wang, He; Yang, Minghe; Jin, Shuangling; Zhang, Rui; Li, Weifeng; Wang, Yan; Huo, Wanying; Wang, Xiaorui; Qiao, Wenming; Ling, Licheng; Jin, Minglin
Abstract: MnOx −CeO2 /P‐CA catalysts were prepared via incipient wetness impregnation of Mn(NO3 )2  ⋅ 4H2 O and Ce(NO3 )3  ⋅ 6H2 O over phosphorus‐doped carbon aerogels (P‐CA) for selective catalytic reduction of NO by NH3 (NH3 −SCR). The results show that P doping on carbon support significantly promotes the NH3 −SCR performance of MnOx −CeO2 /P‐CA catalysts. P modification can improve the hydrophilicity of carbon support and facilitate the dispersion of MnOx −CeO2 components on carbon surface, which enhances the electronic interactions between MnOx and CeO2 . The optimal catalyst 10 %MnOx −CeO2 /P‐CA shows higher surface acidity, more Mn 4+ and Ce 3+, and a larger amount of surface chemisorbed oxygen (Oα ) than that of 10 %MnOx −CeO2 /CA catalyst. As a result, even though in the company of SO2, more NO can be adsorbed and oxidized over the 10 %MnOx −CeO2 /P‐CA catalyst to generate more NO complexes, alleviating the suppression of SO2 on the SCR reaction via Langmuir‐Hinshelwood (L−H) mechanism, and thus the SO2 resistance is enhanced. Abstract : P doping can promote the highly dispersion of MnOx and CeO2 species on carbon support and enhance the interaction between MnOx and CeO2 . The 10 %MnOx −CeO2 /P‐CA catalyst possesses stronger surface acidity, more Mn 4+ and Ce 3+, and larger amount of surface chemisorbed oxygen (Oα ) than that of 10 %MnOx −CeO2 /CA catalyst. More NO complexes can be generated on 10 %MnOx −CeO2 /P‐CA to alleviate the suppression of SO2 on the SCR reaction via L−H mechanism.